Mobilitas Manusia dan Tingkat Penyebaran Covid-19: Sebuah Analisis Kuantitatif - Arkham Zahri Rakhman; Lukito Edi Nugroho (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2021)
The Covid-19 pandemic has created many uncertainties and decisions are often made without the support of undisputable facts. The presentation of facts based on quantitative data becomes an important factor to improve the quality of decisions. This paper aims at building support for pandemic fact provisioning through a quantitative approach. Using community mobility data and data on Covid-19 daily transmission rate, this study analyzes the correlation between these two factors in the Special Region of Yogyakarta. Correlation was calculated between daily Covid-19 transmission rate and community mobility in six types of areas that could be linked to social gathering. In the time span between March 2020 and March 2021, the correlation between the daily transmission rate and community mobility in all areas was low (correlation coefficient between 0.03 and 0.33). The result explained that reduced community mobility developed social distancing, which was effective in controlling virus transmission. However, in shorter time spans which contain spikes in mobility to public destination areas triggered by several long holidays, the correlation between the increase of daily Covid-19 cases and the ‘stay at home’ activity increased significantly (correlation coefficient 0,64). This showed the fact that Covid-19 spread is characterized more by family clusters.